2021
DOI: 10.1186/s41072-021-00085-3
|View full text |Cite
|
Sign up to set email alerts
|

Conditions influencing the choice between direct shipment and transshipment in maritime shipping network

Abstract: This study examines the conditions that influence the choice between direct shipment and transshipment, focusing on two factors: geographical distance and demand. We develop a two-stage model comprising shipping lines and shippers, and apply it to a virtual maritime network with one origin, two destination ports, and one hub port. The generalized costs of shippers in the optimum direct shipment and in transshipment for the shipping lines model are compared to evaluate the choice between direct shipment and tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…In their case, direct routing turned out to be more economical than using the transshipment nodes. Tagawa et al (2021) also examined the alternative of direct shipping and transshipment in their paper. Sherali et al (1999) analyzed fleet management models and algorithms for oil tanker routing and scheduling.…”
Section: Methodsmentioning
confidence: 99%
“…In their case, direct routing turned out to be more economical than using the transshipment nodes. Tagawa et al (2021) also examined the alternative of direct shipping and transshipment in their paper. Sherali et al (1999) analyzed fleet management models and algorithms for oil tanker routing and scheduling.…”
Section: Methodsmentioning
confidence: 99%
“…The study also identified the challenges that need to be addressed for freight by short sea shipping operations to compete effectively with all-truck routes. Tagawa et al [5] analyzed factors influencing mode-choice decisions in maritime shipment network also pointing out the importance of incorporating qualitative attributes to the analysis.…”
Section: Introductionmentioning
confidence: 99%